PREDICTORS OF EMPLOYEE ENGAGEMENT IN MALAYSIA, AND THE MODERATING EFFECTS OF JOB DEMANDS AND TOTAL REWARD - Akmal Latiff Ayob; Norzanah Mat Nor (Asian Academy of Management Journal, 2019)
As reported by Aon Hewitt in 2015 and 2017, there are still a lot of countries, including Malaysia, that recorded the employee engagement score below the global average value of 65%. Malaysia’s employee engagement score values were recorded at 61% and 59% for years 2015 and 2017, respectively. Low quality condition of new vehicles produced by Malaysia’s national automotive manufacturing companies is potentially caused by non-engaged employees. In academic literature, Job Demand-resource (JD-R) is the most widely used theory in employee engagement study. However, there are still a few gaps associated with the theory (i.e., inconsistence finding). In addressing the research gaps, this present study aims to examine whether job-related variables (i.e., job characteristics and job demands), personal-related variable (i.e., positive psychological capital), and environmental-organisational related variable (i.e., total reward) influence employee engagement. The relationships among the variables were explained using two selected theories, namely the JD-R theory, and Self Determination theory. This study makes several significant contributions to practitioners and theories especially on the employee engagement context. Generally, findings from the study significantly contributed knowledge to practitioners especially from Malaysia’s national automotive manufacturing companies on the major factors influencing employee engagement for them to understand, describe, and explain. In addition, for the theories, the study added to the general body of knowledge and current research work on the effects of job-related variables (i.e., job characteristics and job demands), personal-related variable (i.e., positive psychological capital), and organisational-environmental related variable (i.e., total reward) on employee engagement.